What effect do vocational training vouchers have on the unemployed? - Anthony Strittmatter (IZA World of Labor, 2016)
The objective of providing vocational training for the unemployed is to increase their chances of re-employment and human capital accumulation. In comparison to mandatory course assignment by case workers, the awarding of vouchers increases recipients' freedom to choose between different courses and makes non-redemption a possibility. In addition, vouchers may introduce market mechanisms between training providers. However, empirical evidence suggests that voucher allocation mechanisms prolong the unemployment duration of training participants. But, after an initial period of deterioration, better long-term employment opportunities are possible.
Keywords: J38; J68; H43; 330; voucher; assignment mechanism; consumer sovereignty; vocational training; unemployment